Multimodal lung cancer screening using the ITALUNG biomarker panel and low dose computed tomography. Results of the ITALUNG biomarker study. Issue 1 (21st April 2017) - Carozzi, Francesca Maria; Bisanzi, Simonetta; Carrozzi, Laura; Falaschi, Fabio; Lopes Pegna, Andrea; Mascalchi, Mario; Picozzi, Giulia; Peluso, Marco; Sani, Cristina; Greco, Luana; Ocello, Cristina; Paci, Eugenio; et al.
Abstract : Asymptomatic high‐risk subjects, randomized in the intervention arm of the ITALUNG trial (1, 406 screened for lung cancer), were enrolled for the ITALUNG biomarker study ( n  = 1, 356), in which samples of blood and sputum were analyzed for plasma DNA quantification (cut off 5 ng/ml), loss of heterozygosity and microsatellite instability. The ITALUNG biomarker panel (IBP) was considered positive if at least one of the two biomarkers included in the panel was positive. Subjects with and without lung cancer diagnosis at the end of the screening cycle with LDCT ( n  = 517) were evaluated. Out of 18 baseline screen detected lung cancer cases, 17 were IBP positive (94%). Repeat screen‐detected lung cancer cases were 18 and 12 of them positive at baseline IBP test (66%). Interval cancer cases (2‐years) and biomarker tests after a suspect Non Calcific Nodule follow‐up were investigated. The single test versus multimodal screening measures of accuracy were compared in a simulation within the screened ITALUNG intervention arm, considering screen‐detected and interval cancer cases. Sensitivity was 90% at baseline screening. Specificity was 71 and 61% for LDCT and IBP as baseline single test, and improved at 89% with multimodal, combined screening. The positive predictive value was 4.3% for LDCT at baseline and 10.6% for multimodal screening. Multimodal screening could improve the screening efficiency at baseline and strategies for future implementation are discussed. If IBP was used as primary screening test, the LDCT burden might decrease of about 60%. Abstract : What's new? Low‐dose computed tomography (LDCT) for lung cancer screening is associated with a high frequency of detection of pulmonary nodules of uncertain clinical significance. Here, to better identify high‐risk individuals, LDCT was combined with biomarker detection as part of ITALUNG, an LDCT lung cancer screening trial in Italy. The ITALUNG Biomarker Panel (IBP), consisting of plasma DNA quantification, loss of heterozygosity, and microsatellite instability, showed high sensitivity for lung cancer detection at baseline screening. Specificity increased to 89% with the multimodal approach, suggesting that combined use of LDCT and IBP can significantly improve the effectiveness of lung cancer screening.